Intertester agreement and validity of identifying lumbar pain provocative movement patterns using active and passive accessory movement tests - Hidalgo, B.; Hall, Toby; Nielens, H.; Detrembleur, C. (Elsevier Inc, 2014)
Objective: The purpose of this study was to evaluate the interexaminer agreement and validity of active and passive pain provocation tests in the lumbar spine. Methods: Two blinded raters examined 36 participants, 18 of whom were asymptomatic and 18 reported subacute nonspecific low back pain (LBP). Two types of pain provocation tests were performed: (1) physiological movements in single (flexion/extension) and, when necessary, combined planes and (2) passive accessory intervertebral movement tests of each lumbar vertebra in prone with the lumbar spine in neutral, flexion, and extension position .Results: The interobserver agreement in both groups was good to excellent for the identification of flexion (κ =0.87-1) or extension (κ =0.65-0.74) as the most painful pattern of spinal movement. In healthy participants, 0% was identified as having a flexion provocative pattern and 8.8% were identified as having an extension provocative pattern. In the LBP group, 20% were identified as having flexion provocative pattern vs 60% with an extension provocative pattern. The average interexaminer agreement for passive accessory intervertebral movement tests in both groups was moderate to excellent (κ =0.42-0.83). The examiners showed good sensitivity (0.67-0.87) and specificity (0.82-0.85) to distinguish participants with LBP using this combined examination procedure. Conclusion: The use of a combination of pain provocative tests was found to have acceptable interexaminer reliability and good validity in identifying the main pain provocative movement pattern and the lumbar segmental level of involvement. These pain provocation tests were able to distinguish participants with LBP from asymptomatic participants and may help clinicians in directing manual therapy treatment.